Evaluasi Proses Produksi Country kettle Pada PT PLB Dengan Pendekatan Lean Maufacturing - Lina Aulia (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2021)
PT PLB (pseudonym) is a company that produces household appliances and kitchen utensils. The country kettle is one type of product made by PT PLB. The productivity of the country kettle production line decreased by 56%. This was due to defective products. The largest percentage of defects in-country kettle products occurred in the spinning process of 40.18%. This study aimed to identify the causes of defects in-country kettle products and how to overcome them by designing improvement proposals. Lean manufacturing principles were used to evaluate the problems that occur. There were three types of lean manufacturing tools used in this study: Value Stream Mapping (VSM) and 5Ways. VSM was used to describe and identify value-added activities, non-value-added activities but necessary, and non-value-added activities so that the production process becomes lean. The root cause analysis was performed using the 5 Whys method. Unskilled workers and non-standard material types between suppliers are the highest contributors to defects in the spinning process. Based on this, this research was focused on improvements made in the spinning process. Proposals for improvements to the causes of the problems found are standardization of work procedures, standardization of supplier specifications, and arrangement of semi-finished goods and/or supplies. Based on the company's results, the proposed standardization of work procedures and arrangement of semi-finished goods and/or supplies may be implemented in the company. Meanwhile, the proposal for selecting suppliers is not feasible due to company limitations